Impact of the COVID-19 pandemic on the seasonality of respiratory syncytial viral infection - I. V. Babachenko; E. D. Orlova; Yu. V. Lobzin (Журнал инфектологии)
The article presents an overview of current trends in the epidemiology of respiratory syncytial viral (RSV) infection, including its seasonality, under the impact of the COVID-19 pandemic, both according to world literature and taking into account monitoring epidemiological studies conducted in the Russian Federation. A detailed description of the dynamics of RSV detection in the period 2020-2021 and the beginning of 2022 in Russia according to the results of the all-Russian epidemiological monitoring is given. Epidemiological studies in different regions of the world, including Russia, have revealed the absence of seasonal rises in the incidence of RSV infection, characteristic of previous years, in 2020 and winter-spring in 2021 under the influence of the COVID-19 pandemic. In 2021-2022, a sharp increase in the incidence and hospitalization of children was noted against the back-drop of a decrease in cases of a new coronavirus infection in all countries of the world, while the start time and duration of respiratory syncytial virus infection, typical for the prepandemic period, changed. Our previous studies have shown that in different years and in different regions of Russia, the start and end times of the epidemiological season may also not coincide, which makes it difficult to predict seasonal peaks in incidence, their duration and severity only on the basis of previously obtained data. This makes it expedient to extend the terms of passive specific prophylaxis with palivizumab for a year if there are indications for its use, including taking into account the data of epidemiological monitoring conducted in the Russian Federation.